Characterization of putative methyltransferase MT420 in Trypanosoma brucei. - Procházková, Michaela (Jihočeská univerzita, 2010)
Localization and characterization of putative mitochondrial methzltransferase acc. No.: Tb10.6k15.0440 in Trypanosoma brucei was performed. Employed molecular methods included immunofluorescence, sub-cellular fractionation and tandem affinity purification. Protein was overexpressed in an E. coli expression system, using an in-fusion expression vector pOPINM with maltose binding protei (MBP) tag.
Characterization of putative methyltransferase MT420 in Trypanosoma brucei.
Keywords: SAM-dependent methyltransferase; mitochondrion; translation release factor; localization; MBP fusion protein